2014
DOI: 10.1097/scs.0000000000000524
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Keratinized Tissue Augmentation During Implant Rehabilitation After Le Fort I Osteotomy

Abstract: The aim of this study was to test a new collagen matrix (Mucoderm) positioned during oral implant abutment connection. A patient previously treated with Le Fort I for bone augmentation and 8 implants showing minimal amount of keratinized tissue was selected for an extensive keratinized tissue augmentation and deepening of the oral vestibule by apically positioning a split palatal flap and palatal grafting with Mucoderm. Clinical data at 9 and 14 days and 1 and 2 months showed resorption of the collagen graft, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
0
18
0
4
Order By: Relevance
“…, Nocini et al. ). Originally, such collagen matrices were introduced to promote keratinized tissue regeneration and in the further course subsequently used for root coverage procedures (Sanz et al.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…, Nocini et al. ). Originally, such collagen matrices were introduced to promote keratinized tissue regeneration and in the further course subsequently used for root coverage procedures (Sanz et al.…”
mentioning
confidence: 98%
“…As alternative to SCTGs, xenogeneic soft tissue substitutes such as porcine-derived 3D collagen-based matrices are currently in the focus, with the intention to avoid postoperative patient morbidities and risks associated with autologous tissue grafting (Sanz et al 2009, Ghanaati et al 2011, Schmitt et al 2013, Nocini et al 2014. Originally, such collagen matrices were introduced to promote keratinized tissue regeneration and in the further course subsequently used for root coverage procedures (Sanz et al 2009, Herford et al 2010, McGuire & Scheyer 2010, Nevins et al 2011, Zuhr et al 2014.…”
mentioning
confidence: 99%
“…In clinical practice, the subepithelial connective tissue graft (SCTG) is regarded as the gold standard for such procedures (Jung, Siegenthaler, & Hammerle, 2004;Schwarz et al, 2014;Sculean et al, 2015;Thoma et al, 2014;Zuhr, Baumer, & Hurzeler, 2014). However, autologous tissue grafting is associated with postoperative patient morbidities and operative risks, motivating investigations of potential alternatives, such as porcine-derived 3D collagen-based matrices (Bassetti et al, 2016;Ghanaati et al, 2011;Nocini et al, 2014;Sanz, Lorenzo, Aranda, Martin, & Orsini, 2009;Schmitt et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, current research focuses on alternative techniques and materials. A porcine acellular dermal collagen matrix (CM) has been introduced as an alternative to SCTGs in order to avoid surgical risks and to decrease patient morbidity . These matrices proved their ability to increase soft tissue thickness in preclinical animal studies .…”
Section: Introductionmentioning
confidence: 99%
“…A porcine acellular dermal collagen matrix (CM) has been introduced as an alternative to SCTGs in order to avoid surgical risks and to decrease patient morbidity. [15][16][17][18][19] These matrices proved their ability to increase soft tissue thickness in preclinical animal studies. [20][21][22] In a comparative dog study, a porcine CM has shown similar results as SCTG after a 10-month follow-up.…”
Section: Introductionmentioning
confidence: 99%